Effects of Air Injection on the Metabolic Activity of Emulsifier-Producing Bacteria from Oil Reservoirs. (10th February 2020) - Gu, Yi; Wu, Zhenzhen; Wang, Guan; Zhi, Bo; Yu, Jiliang; Fan, Huiqiang; Guo, Suzhen; Ma, Ting; Li, Guoqiang
Abstract : Oil emulsification is one of the major mechanisms for microbially enhanced oil recovery (MEOR). Although air injection is generally recommended for field trials of MEOR in China, its influence on the microbial community structure in oil reservoirs remains poorly understood, especially activation of emulsifier-producing bacteria. Herein, the effects of air injection on oil emulsification, nutrient consumption, oil properties, and microbial community structures were compared for activated cultures under four different oxygen content conditions: anaerobic, facultative anaerobic, intermittent aeration, and aerobic. The results showed that crude oil in aerobic and intermittent aeration cultures was emulsified effectively when nutrients were thoroughly depleted. The particle diameter of emulsified droplets was 4.74-10.02 μ m. High-throughput sequencing results showed that Bacillus and Aeribacillus were effectively activated under aerobic and intermittent aeration conditions, while Tepidimicrobium and Coprothermobacter were activated under facultative anaerobic and anaerobic conditions. Real-time quantitative PCR results showed that the initial emulsifying effect was positively correlated with the abundance of Aeribacillus pallidus .